(untitled) (British Journal of Multidisciplinary and Advanced Studies, 2023)
This study set out to analyse the influence of leadership styles on organizational performance with reference to the Commission Nationale Indépendante des Droits de l’Homme. The study employed correlational research design and opted a quantitative approach. Survey questionnaire was used to collect data from the accessible population of 41. The results indicate that there is a positive and significant relationship between Transformational leadership and organizational performance (r=.589, p-value<.01); a positive and significant relationship between Transactional leadership and organizational performance (r=.745, p-value<.01); and There findings indicate also a positive and significant relationship between Laissez-faire leadership and organizational performance (r=.562, p-value<.01); a positive and significant relationship between Autocratic leadership and organizational performance (r=.655, p-value<.01). The results show also that Transformational leadership, transactional leadership, laissez-faire leadership, and autocratic leadership explain 59.2% of the variation in organizational performance (Adjusted R2=.592). Therefore, the institution and the government should effectively encourage the use of different leadership styles as long as they all contribute to the performance of the institution.